Շրջասությամբ ոճավորված դարձվածքները հայերենում, ռուսերենում և անգլերենում - Հ. Զ. Ղազարյան (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
Одним из самых распространенных способов переосмысления свободных и устойчивых словосочетаний является перифраз, представляющий собой описательное выражение, иносказание, описательно выражающее одно понятие с помощью нескольких. Частным случаем перифраза является эвфемизм – описательное выражение “низких” или “запретных” понятий. One of the most widespread forms of semantic change of free and fixed collocations is periphrasis which is a device, denoting the use of a longer phrasing in place of a possible shorter and plainer form of expression. It is also called circumlocution due to the round-about or indirect way used to name a familiar object or henomenon. A variety of periphrasis is the euphemism which is a word or a phrase used to replace an unpleasant word or expression by a conventionally more acceptable one.
Keywords: Լեզու և գրականություն; Հայոց լեզու